1968
DOI: 10.1002/apmc.1968.050040108
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetale mit reaktiven gruppen

Abstract: Zur Einfuhrung reaktiver Giwppen in Polyacetale kommen im wesentlichen drei Wege in Frage:1. Umsetzung der OH-Endgruppen mit geeigneten Reagenzien, 2. Einbau durch eine ubertragungsreaktion wahrend der Polymerisation, 3. Copolymerisation von Trioxan oder von Formaldehyd rnit Monomeren rnit funktionellen Gruppen.Die Copolymerisation von Trioxan rnit Monomeren, die eine zusatzliche reaktive Gruppe besitzen, wird ausfuhrlich besprochen ; hier haben sich substituierte Phenylglycidylather als Conionomere gut bewahr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several modified‐POM samples have been prepared, containing a variety of reactive groups as side chain branches from the main polymer backbone and as terminal groups on the polymer chain 14–20. Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19.…”
Section: Introductionmentioning
confidence: 99%
“…Several modified‐POM samples have been prepared, containing a variety of reactive groups as side chain branches from the main polymer backbone and as terminal groups on the polymer chain 14–20. Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19.…”
Section: Introductionmentioning
confidence: 99%
“…The results provide possibilities for further and comprehensive improvements in the compatibility with glass binders and, therefore, the mechanical properties of glass‐fiber‐filled POM. Additionally, several modified POM samples have been prepared containing a variety of reactive groups as side‐chain branches from the main polymer backbone and as terminal groups on the polymer chain 17–23. Wissbrun22 reported that a POM copolymer of TOX with epichlorohydrin as a comonomer reacted with thioglycolate to produce a modified POM with carboxylic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…3-(l,2-Diacetoxyethyl)-a-benzyl-tert-buty lamino-4benzyloxyacetophenone (16). A solution of 15 (4.40 g, 9.8 mmol) and tert-butylbenzylamine (3.04 g, 18.6 mmol) in 50 mL of MeCN was refluxed for 3.5 h. To the chilled solution was added 100 mL of Et^O, and the insoluble material was filtered. The filtrate was concentrated to leave a residue which was chromatographed on an alumina column (eluted with CHCl3-hexane 3:2).…”
Section: -Benzyloxy-3-(l2-dihydroxyethyl)acetophenone (14a)mentioning
confidence: 99%